2017
DOI: 10.1093/ntr/ntw222
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Maternal Smokers Who Quit During Pregnancy: A Population-Based Cohort Study of Tasmanian Women, 2011–2013

Abstract: Smoking cessation interventions have traditionally targeted socially disadvantaged women, for good reason: the majority of smoking pregnant women fall into this category. However, despite the significant attention and resources dedicated to antenatal smoking cessation interventions, most are ineffective with only 7.6% of the present sample quitting smoking during pregnancy. This paper may assist in developing more effective antenatal smoking cessation interventions by more clearly describing the profile of mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
1
6
0
1
Order By: Relevance
“…Smoking and alcohol during pregnancy may act synergistically to harm the health of the child 29 . Living in an area of greater socioeconomic disadvantage was associated with maternal smoking during pregnancy, which is supported by earlier studies in Australia 2,30 and elsewhere 31 . The disparity in smoking levels during pregnancy between women living in areas with different socioeconomic status suggests the need for targeting smoking prevention programs.…”
Section: Discussionsupporting
confidence: 64%
“…Smoking and alcohol during pregnancy may act synergistically to harm the health of the child 29 . Living in an area of greater socioeconomic disadvantage was associated with maternal smoking during pregnancy, which is supported by earlier studies in Australia 2,30 and elsewhere 31 . The disparity in smoking levels during pregnancy between women living in areas with different socioeconomic status suggests the need for targeting smoking prevention programs.…”
Section: Discussionsupporting
confidence: 64%
“…In contrast, it is lower than that of Italy at 23%, [33] and Poland at 34.6% [34]. On the other hand, the percentage of women who quit smoking during pregnancy was lower than the 7.6% as reported by Frandsen and colleagues in 2017 [35].…”
Section: Discussionmentioning
confidence: 65%
“…Based on the findings from the included studies, prenatal/perinatal exposure to active/passive smoke was largely found to increase the risk of developing postpartum depression and depressive symptoms in the postpartum period. Prenatal active smoking was found to be associated with an increased risk for postpartum depression, particularly those who smoked prior to pregnancy and continued to smoke during pregnancy into the postpartum period, compared to those women who quit during pregnancy and those who were non-smokers (Chen et al, 2018;Dagher & Shenassa, 2012;Frandsen, Thow, & Ferguson, 2017;Munafò, Heron, & Araya, 2008;Salimi et al, 2015;Vivilaki et al, 2016). The study by Underwood et al (2017) did not find an association between prenatal active smoking and postpartum depression.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…The main findings of this systematic review suggest that those exposed to active/passive smoke (cigarette/tobacco) during the prenatal/perinatal period had the greatest risk of developing postpartum depression and depressive symptoms in the postpartum period, compared to the other categories of toxicants. The literature does support a link between certain environmental toxicants and postpartum depression (Chen et al, 2018;Dagher & Shenassa, 2012;Frandsen et al, 2017;Munafò et al, 2008;Salimi et al, 2015;Sheffield et al, 2018;Singata-Madiliki et al, 2016;Vivilaki et al, 2016), although there were studies with inconclusive results and/or that found no association. These observations will be further explained throughout the following sections and the results for each category of toxicant will be interpreted.…”
Section: Main Findingsmentioning
confidence: 99%